2016
DOI: 10.4103/0970-0218.173492
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of overweight and obesity among women in an Urban area of North India

Abstract: Background:Obesity is a complex, multi-factorial chronic disease. Overweight and obesity are the fifth leading risk for global deaths.Objectives:To find the prevalence and risk factors for obesity in women aged 20-60 years in Ludhiana city.Methods:The present study is a community based cross sectional study carried out in an urban area of Ludhiana among women aged 20-60 years. Among the study population of 324 women, a pre-designed and pre-tested questionnaire was used to record the socio-demographic and anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 4 publications
(3 reference statements)
0
23
0
2
Order By: Relevance
“…1,2,4,36,40,44 Recent studies have documented populations of the country to exhibit a high prevalence of overweight or obesity. 4,21,25,32 The prevalence of undernutrition is also a serious problem among the adult populations of East and Northeast India. 5,25,38,66,[67][68][69] Therefore, the co-existence of the DBM (both under and overnutrition) is presenting a unique difficulty for public health policymakers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,4,36,40,44 Recent studies have documented populations of the country to exhibit a high prevalence of overweight or obesity. 4,21,25,32 The prevalence of undernutrition is also a serious problem among the adult populations of East and Northeast India. 5,25,38,66,[67][68][69] Therefore, the co-existence of the DBM (both under and overnutrition) is presenting a unique difficulty for public health policymakers.…”
Section: Discussionmentioning
confidence: 99%
“…A steady increase in the prevalence of overweight or obesity has been reported from different Indian populations. 3,[17][18][19][20][21]25,[31][32][33] Recent studies have also suggested that this 'double burden' is becoming increasingly apparent in addition to the burden of non-communicable diseases affecting developing countries such as India. 2,10,22,34,35 However, undernutrition still remains a consistent public health problem among populations in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] As in developed societies, the risk for obesity in developing countries like India is also strongly influenced by diet and lifestyle, which are changing dramatically as a result of the economic and nutrition transition. [ 10 ] According to WHO global estimates, about 13% of the world's adult population (11% of men and 15% of women) were obese in 2014. [ 11 ] The prevalence of obesity varies according to age, sex, and region.…”
Section: Introductionmentioning
confidence: 99%
“…En general, y dependiendo del grupo de edad estudiado y del país, la prevalencia de sobrepeso se encuentra entre un 12,7% y 43,2% y de obesidad entre un 11 y 42% (1,(3)(4)(5)(6). Esta variación en la prevalencia es debido a las características de las razas, tipo de alimentación entre otros factores (7).…”
Section: Introductionunclassified